PENGARUH PENERAPAN SISTEM AKUNTANSI KEUANGAN DESA DAN KUALITAS APARATUR DESA TERHADAP KINERJA KEUANGAN DESA KECAMATAN PULAU RAKYAT KABUPATEN ASAHAN - Nuri Jelita Sinaga; Syofyan .; Mas`ut .; Abdul Rasyid (Universitas Islam Islam Sumatera Utara, 2021)
The government accounting system is a systematic series of procedures, operators, equipment, and other elements to realize the accounting function from transaction analysis to financial reporting within government organizations. Quality is defined as the whole of a product, person and process or system that can meet expectations (expectations) or meet the desired satisfaction. Quality human resources are supported by educational backgrounds, often attend education and training and have experience in finance. The performance of village financial management determines whether or not village goals are achieved. Poor financial management performance which is characterized by inconsistent and standardized recording and reporting can make the process of evaluating the use of funds difficult to do. About village financial management implies the importance of applying the principles of transparency, accountability, participatory in the preparation of village finances. Village financial system. In addition to the need for adequate competence and understanding of accounting from each individual, adequate supervision is also needed in managing the village financial system. The management of village finances is still lacking in supervision and lack of tightening of the use of the budget. This study aims to determine the village financial accounting system and the quality of the village apparatus on village financial performance in Pulau Rakyat Subdistrict, Asahan Regency and find out whether the village financial accounting system and the quality of the village apparatus on village financial performance are in accordance with the theory and techniques of the accounting system carried out in this study. by distributing questionnaires.